Supervisi Klinis Berkelanjutan Mampu Meningkatan Kompetensi Guru Dalam Penerapan Pembelajaran Project Based Learning - Sugiyah Sugiyah (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
Teachers feel burdened with a lot of materials to accomplish ASPD, PTS, and PAS in limited face-to-face learning (PTMT) where students only study at school for a maximum of 3 hours per day. Based on the observations of the researcher, currently teachers are still using conventional learning methods. This study aimed to improve the competence of teachers in the upper grades in implementing PJBL at SD Negeri Conegaran through sustainable clinical supervision. This research used a descriptive qualitative method of action research, with comparative descriptive data analysis through observation and documentation. The researcher conducted sustainable clinical supervision for teachers of grades IV, V, and VI. The research consisted of 2 cycles and each cycle consisted of 2 meetings with the stages of planning, implementing, observing, and reflecting. The research was conducted from February to May 2022. After sustainable clinical supervision was carried out, the result showed that the implementation of PJBL cycle I at the 1st meeting yielded a score of 80.00 (moderate category) and in cycle II at the 2nd meeting yielded a score of 96.47 (very good category). It showed that there was an increase by 16.47 points or 20.58%. Hence, it can be concluded that the implementation of sustainable clinical supervision can improve teacher competence in implementing PJBL in the upper grades.